Effectiveness of Financing Measures to Reduce Low Emissions in Poland - a Case Study - Godzisz, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Local authorities are increasingly facing the challenges of climate change, which requires adaptation of various elements of local government systems, including infrastructure, communities and local economies. Operating in an ever-changing reality, local government units should plan for the necessary sustainable local government investments, with particular attention to structural gaps and financial mismatches. Local government is responsible for ensuring local energy security and thus for "environmental sustainability".
Keywords: effectiveness; low carbon economy; air pollution; low emissions; local government